Pemberian Kascing, Glomus sp., dan Agrobacterium pusense untuk Meningkatkan Kolonisasi Akar, Serapan P, dan Pertumbuhan Kedelai Hitam (Glycine max (L.) Merrill) pada Inceptisols Jatinangor - Nurbaity, Anne; Dristiarini, Raia Zaviera; Yuniarti, Anni (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2025)
Low soil fertility was a major factor limiting national black soybean productivity. Black soybean, a functional food crop rich in isoflavones, requires effective fertilization to enhance growth.Environmentally friendly alternatives such as vermicompost and biofertilizers offer sustainableoptions. This study aimed to evaluate the effects of vermicompost and biofertilizers on rootcolonization by arbuscular mycorrhizal fungi (AMF), phosphorus (P) uptake, and black soybeangrowth, and to identify the most effective treatment. The experiment was conducted from December2024 to February 2025 in a plastic house at Bale Tatanen, Faculty of Agriculture, UniversitasPadjadjaran, Jatinangor, West Java. A Randomized Group Design with 12 treatment combinations andthree replications was used. Treatments consisted of 5 and 10 tonnes ha⁻¹ of vermicompost combinedwith either AMF or nitrogen-fixing bacteria (NFB), which were appllied to the planting holes. Datawere analyzed using ANOVA and the Scott-Knott test at a 5% significance level. Observed parametersincluded AMF root colonization, P uptake, plant height, number of leaves, chlorophyll index, leaf area,and dry weights of roots and shoots. The results showed that vermicompost and biofertilizersincreased AMF colonization, P uptake, plant height, leaf number, chlorophyll index, and shoot dryweight. The application of 5 tonnes ha⁻¹ vermicompost combined with AMF was the most effectivetreatment. This study provided useful recommendations for vermicompost and biofertilizerapplication to support soil fertility improvement and black soybean growth on marginal lands.